Essentials of development economics - Taylor, J. Edward; Lybbert, Travis J. (University of California Press, 2020)
"Written to provide students with the critical tools used in today's development economics research and practice, Essentials of Development Economics represents an alternative approach to traditional textbooks on the subject. Compact and less expensive than other textbooks for undergraduate development economics courses, Essentials of Development Economics offers a broad overview of key topics and methods in the field. Its fourteen easy-to-read chapters introduce cutting-edge research and present best practices and state-of-the-art methods. Most development texts are written around topics: money, labor, population, and so on. The chapters in this book are less about topics than about providing a window into how developing economies are different and how this shapes the way we study them. Most of the cutting-edge research by economists is found in journal articles that are beyond the reach of most undergraduate students. Sidebars scattered throughout the book try to make important research in influential articles accessible, summarizing the questions they ask, the methods they use, key findings, and why they are important. By mastering the material in this book, students will have the conceptual grounding needed to move on to higher-level development economics courses"--